Test anxiety across writing formats: The mediating role of perceived teacher strictness - Abdullah Al Fraidan (Acta Psychologica)
This study examines how different types of writing tasks can influence anxiety among students learning English as a Foreign Language (EFL). Specifically, we explored whether tasks requiring students to correct errors (indirect tasks) cause more anxiety than tasks that involve writing original content (direct tasks like essays or letters). We also investigated if students' perceptions of their teachers as strict affected their anxiety levels during these tasks. A total of 80 university students participated by completing various writing tasks, and 10 instructors shared their views through interviews. The results revealed that students experienced significantly greater anxiety when working on indirect tasks (editing) compared to direct writing tasks (essays or letters). Additionally, students who perceived their instructors as strict reported feeling anxious before starting the tasks, but this anxiety reduced during task performance. Our findings suggest that educators can reduce student anxiety by balancing assessment tasks and maintaining supportive classroom interactions.